2022
DOI: 10.1017/s0033291722003427
|View full text |Cite|
|
Sign up to set email alerts
|

Interpretation bias in health anxiety: a systematic review and meta-analysis

Abstract: Interpretation bias (i.e. the selective negative interpretation of ambiguous stimuli) may contribute to the development and maintenance of health anxiety. However, the strength of the empirical evidence for this association remains a topic of debate. This study aimed to estimate the association between health anxiety and interpretation bias and to identify potential moderators of this association. Chinese-language databases (CNKI, VIP, and Wanfang), English-language databases (Web of Science, PubMed, PsycINFO,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 82 publications
1
3
0
Order By: Relevance
“…Consistent with earlier meta-analyses on the role of IBs in psychopathology (Chen et al, 2020;Du et al, 2023;Everaert et al, 2017), we found that direct measures were associated with considerably larger effect sizes compared to indirect measures (e.g., relying on reaction times), to the point that the effect size for indirect measures was not statistically significant. This suggests that the current evidence on IBs in anxiety is limited to direct measures while indirect measures suggest an absence of the association.…”
Section: Under What Assessment Conditions Are Ibs Observed In Anxiety?supporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with earlier meta-analyses on the role of IBs in psychopathology (Chen et al, 2020;Du et al, 2023;Everaert et al, 2017), we found that direct measures were associated with considerably larger effect sizes compared to indirect measures (e.g., relying on reaction times), to the point that the effect size for indirect measures was not statistically significant. This suggests that the current evidence on IBs in anxiety is limited to direct measures while indirect measures suggest an absence of the association.…”
Section: Under What Assessment Conditions Are Ibs Observed In Anxiety?supporting
confidence: 91%
“…IBs are transdiagnostic (risk) factors and thus characterize multiple mental disorders, for instance depression (Everaert et al, 2017), disorders from the obsessive-compulsive spectrum such as health anxiety (Du et al, 2023), or eating disorders (e.g., Korn et al, 2020). Several studies testing whether (anxiety-disorder specific) IBs are present have compared anxious samples to non-anxious clinical samples in addition to healthy controls (e.g., .…”
Section: Control Group Statusmentioning
confidence: 99%
“…A study on self-reported intentions to receive the covid-19 vaccine among vaccine hesitant individuals found similar worries about the vaccine safety and possible side-effects ( 37 ). Little trust in the reassurances and interventions by health authorities might occur in relation to HA ( 38 , 39 ). This lack of trust in health authorities may exacerbate insecurity and increased anxiety during the pandemic in families.…”
Section: Discussionmentioning
confidence: 99%
“…A key contribution to this misinterpretation is an attentional bias towards health-threat related stimuli, which has shown to be strongly associated with health anxiety in a recent systematic review and meta-analysis [ 46 ]. Health-anxious individuals have also been shown to experience more frequent and intense illness-related intrusive thoughts [ 47 , 48 ], and to demonstrate a selective negative interpretation bias of these thoughts or sensations [ 49 ].…”
Section: Cognitive and Behavioural Aspects Of Health Anxietymentioning
confidence: 99%